Self Portrait with wife and models: A Semiotic analysis (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The following article presents the Semiotic Analysis of Self Portrait with wifeand models, Paris, 1981, by the german photographer Helmut Newton (Photograph Nº 17), which is included in his memorable briefcase named Private Property. These photograph is undertaken fundamentally from Peirce's perspective (1986) in theoretical dialogue with the levels of the image of Barthes (1986), and Panofsky's iconologic methodology (1970). The results of the investigation shows the erotic character of Newton's photography that constitutes its legisign, the presence of multiple histories and intertextual relations that declare a summary of the personal history of the author and staging of the female body as a contradictory element to the traditional esthetic codes of the fashion industry.
Keywords: Semiotic analysis; erotic photography; legisingn; self-portrait